(untitled) (International Journal of Engineering Sciences & Management Research, 2015)
Banks play an important role in the economic development of every nation. They have control over a large part of the supply of money in circulation. A bank is a financial intermediary that accepts deposits and channels those deposits into lending activities. Banks are a fundamental component of the financial system, and are also active players in financial markets. The paper studies the loan performance of selected public banks. Last decade has witnessed many changes in the banking industry. In this study highlighted the effect of the loans and advances on the Indian Economy. Banks mainly make profit from the difference of interest received and loans paid. Banks are performing the number of functions in addition to its two main functions lending and accepting deposits. Banks grant loans in order to satisfy the growing credit needs of the different sections of the society but since the Commercial banks are profit making Organization thus they have profit making dimension added to advances granted by them. In this paper we have focused on the movement of Loans of the public banking industry by analyzing the data from the year 2009-10 to 2013-14.